Analiza strategii przedsiębiorstwa oraz kierunków jej realizacji na przykładzie wybranych jednostek gospodarczych - Jaworska, Elżbieta; Łagodzki, Przemysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article presents the issues of firm's goals and theirs role in the company. It also demonstrates the essence of the strategy, its dimensions and the functions, which strategy realizes. In the article is made an attempt to analyse of corporate strategy and its ways of realization on the example of group of chosen enterprises, quoted on Warsaw Stock Exchange, which belong to the wood and paper industry. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 78-87